2010
DOI: 10.1007/s12272-010-1107-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen activated protein kinases are prime signalling enzymes in nitric oxide production induced by soluble β-glucan from Sparassis crispa

Abstract: Sparassis crispa (SC) is an edible mushroom that harbours β-glucans reported to possess immunostimulatory and anticancer properties. The role of SC in regulating the functional activation of macrophages is yet to be fully elucidated. The objective of this study was to investigate the molecular mechanism underlying the immune-stimulatory function of Sparassis crispa soluble β-glucan (Sc-SG) on macrophages. According to this study, Sc-SG was able to stimulate nitric oxide (NO) production as well as enhance the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Based on in vitro studies, ␤-glucans act on several immune receptors, e.g. dectin-1 and trigger a group of immune cells including monocytes, macrophages, neutrophils, natural killer cells and dendritic cells [3,[11][12][13][14]. The entire signaling pathway downstream to dectin-1 activation leads to the release of cytokines including interleukin IL-12, IL-6, tumor necrosis factor (TNF), and IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…Based on in vitro studies, ␤-glucans act on several immune receptors, e.g. dectin-1 and trigger a group of immune cells including monocytes, macrophages, neutrophils, natural killer cells and dendritic cells [3,[11][12][13][14]. The entire signaling pathway downstream to dectin-1 activation leads to the release of cytokines including interleukin IL-12, IL-6, tumor necrosis factor (TNF), and IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, some studies demonstrated more than two healing effects of the mushroom [ 7 , 26 , 28 , 29 , 30 ]. Simultaneously, the anti-diabetic, anti-tumor, anti-inflammatory, anti-fungal, and antioxidant activities of S. crispa were reported in seven [ 6 , 12 , 14 , 28 , 29 , 30 , 31 ], nine-teen [ 7 , 13 , 15 , 21 , 23 , 24 , 26 , 28 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], four [ 7 , 22 , 30 , 42 ], three [ 19 , 29 , 43 ], and six [ 8 , 25 , 26 , 27 , 44 , 45 ] studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From nine-teen studies [ 7 , 13 , 15 , 21 , 23 , 24 , 26 , 28 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], seven reported an anti-tumor activity, five showed an inhibition of cancer cell viability, and nine indicated IFN- induction of S. crispa extracts. On the other hand, there are several reports which showed appropriate data in many respects [ 3 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that phosphorylation of Ser 727 in STAT1 is upregulated by the activation of the MAPK pathway21. In addition, the MAPK pathway is known to be activated after stimulation with β-glucan27. Therefore, the MAPK pathway may possibly be involved in the Ser 727 phosphorylation of STAT1 induced after stimulation with AP-PG.…”
Section: Discussionmentioning
confidence: 98%